From Tragedy to Reconciliation: Advocacy, Legal Strategies, and the Role of History Teachers in Integrating Peace Education in Post-Conflict Areas - Ahmad, Tsabit Azinar; Nurasiah, Nurasiah; Amin, Syaiful; Sohabudin, Ahmad; Arifin, Ridwan (Universitas Negeri Semarang, 2025)
Indonesia’s post-conflict regions, such as Aceh, Poso, and Papua, continue to confront the legacies of violence, trauma, and contested historical narratives. In these areas, history education holds significant potential for promoting reconciliation and preventing the recurrence of conflict. This study examines the role of history teachers in integrating peace education within the broader frameworks of legal strategies and advocacy in Indonesian post-conflict settings. Drawing on qualitative research, including in-depth interviews with educators, civil society actors, and local government representatives, the paper explores how history teachers navigate sensitive political and historical issues in classrooms marked by ethnic, religious, and ideological divisions. The study highlights how legal frameworks such as human rights education, truth-seeking efforts, and transitional justice initiatives—though limited in formal policy—are informally adopted by educators through civil society-led training and community advocacy. Findings suggest that when adequately supported, history teachers in Indonesia can act as frontline peacebuilders, helping students develop critical thinking, historical empathy, and a commitment to nonviolence. Moreover, advocacy networks play a crucial role in enabling educators to address topics such as mass violence, displacement, and state-perpetrated injustice in ways that foster healing rather than deepen polarization. By contextualizing peace education within Indonesia’s unique socio-political landscape, this paper contributes to the global discourse on post-conflict education and provides practical pathways for integrating historical accountability into curriculum and teacher training programs.